Understanding the Past-Present-Future Hydrogeologic System Through Numerical Groundwater Modeling of South Bengal Basin, India - Sikdar, Pradip Kumar; Banerjee, Sumanta; Chakraborty, Surajit (Frontiers in Water, 2022)
Quaternary hydrogeologic system of south Bengal Basin in India with low natural topographic gradients, such as deltas and floodplains, is complex. This complexity can be further compounded by heavy groundwater pumping beneath urban centres and can easily change the groundwater flow paths making the aquifer vulnerable to land subsidence and pollution which may adversely affect the health of millions of people. This research elaborates the hydrogeologic system in and around the twin megacities of Kolkata and Howrah located on this complex delta of south Bengal Basin, and the rapid urbanization pattern during the past thirty years to understand the past, present (2016) and future (2030) behavior of the aquifer system and the advective flow paths of contaminants (wastewater, arsenic and heavy metals) through hydrogeological simulations and field data. The aquifer at present is under a stressed condition: the piezometric surface is declining at a rate of 13-37 cm/year, the groundwater trough in Kolkata is expanding at an exponential rate, at places the confined aquifer is behaving as an unconfined one, threat of land subsidence is increasing, and the water quality is deteriorating. In future the hydrogeological regime of the area may further deteriorate if over-pumping continues. The study also highlights a plan for sustainable development of the stressed aquifer system.